2022
DOI: 10.1002/advs.202103485
|View full text |Cite
|
Sign up to set email alerts
|

A Guanosine‐Quadruplex Hydrogel as Cascade Reaction Container Consuming Endogenous Glucose for Infected Wound Treatment—A Study in Diabetic Mice

Abstract: Diabetic foot ulcers infected with antibiotic‐resistant bacteria form a severe complication of diabetes. Antimicrobial‐loaded hydrogels are used as a dressing for infected wounds, but the ongoing rise in the number of antimicrobial‐resistant infections necessitates new, nonantibiotic based designs. Here, a guanosine‐quadruplex (G4)‐hydrogel composed of guanosine, 2‐formylphenylboronic acid, and putrescine is designed and used as a cascade‐reaction container. The G4‐hydrogel is loaded with glucose‐oxidase and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…After separation and calcination, the G–metal powders were eventually prepared (Figure S1). In our previous research, we found that guanosine, with a ribose ring attached to G via a β- N 9 -glycosidic bond, could form much more stable G-quartet structures in an aqueous solution, yielding hydrogels other than sediments. To simplify the fabrication process, we used G as a building block to construct our complexes in this study.…”
Section: Resultsmentioning
confidence: 99%
“…After separation and calcination, the G–metal powders were eventually prepared (Figure S1). In our previous research, we found that guanosine, with a ribose ring attached to G via a β- N 9 -glycosidic bond, could form much more stable G-quartet structures in an aqueous solution, yielding hydrogels other than sediments. To simplify the fabrication process, we used G as a building block to construct our complexes in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a G-quadruplex hydrogel derived from the self-assembly of guanosine, 2-formylphenylboronic acid, and putrescine was used as a cascade reaction container to produce reactive oxygen species (ROS) from glucose. Furthermore, the multicomponent-derived self-assembled system was reported to have antibacterial activity with excellent in vivo diabetic wound care behavior . However, there are few reports wherein antibiotic-free G-quadruplex hydrogels have been shown to exhibit inherent antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the multicomponent-derived self-assembled system was reported to have antibacterial activity with excellent in vivo diabetic wound care behavior. 38 However, there are few reports wherein antibiotic-free G-quadruplex hydrogels have been shown to exhibit inherent antibacterial activity. The incorporation of nucleobases into the peptide sequence results in the formation of different classes of biomaterials, named nucleopeptides (NPs), 39 and such NPs could be effectively used to form supramolecular hydrogels with potential applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 Recently, a naturally derived guanosine (G)-based supramolecular hydrogel (namely G4 hydrogel) was fabricated via the self-assembly of G and KB(OH) 4 , which involves cation-templated formation of G-quartet motifs and nanofibrils. 25,26 Hemin could be incorporated into G-quartet networks via co-assembly, obtaining an enzyme-like nanofibrous hydrogel (namely H/G4 hydrogel), and polyaniline was further introduced into a H/G4 scaffold by in situ catalytic deposition in order to prepare conductive hybrid hydrogels as biosensors. 27…”
Section: Introductionmentioning
confidence: 99%